A Proposed Educational Supervision Role for Secondary School Principals at Amman District Based on Contemporary Functions of Supportive Educational Supervision - Thaher, Amira (Dirasat: Educational Sciences, 2022)
Objectives: The study aims to propose a supervisory educational support role for principals at public secondary schools at Amman Distirct. This is based on the functions of contemporary educational support for school principals as educational supervisors that support the professional competence of teachers. The study sample consisted of 292 educational supervisors, randomly selected. Methods: The study adopted a developmental survey research method. The study tool was distributed to the sample after extracting the content validity and stability through Crnbach’s alpha coefficient. Results: The results of the study showed that there is a great significance for the existence of a supervisory educational support role for principals of public secondary schools in Amman region based on the functions of contemporary educational support. They also show that there is a need for effective support for school principals in the mastery of supervisory methods, and technical and administrative fields. Conclusions: The proposed supporting supervisory role has been developed to improve the supervisory practices of school principals in an effort to develop the teaching-learning process. The study recommends activating the proposal and employing it among school principals.